2017
DOI: 10.2337/db17-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Myokine Irisin Is Released in Response to Saturated Fatty Acids and Promotes Pancreatic β-Cell Survival and Insulin Secretion

Abstract: This study explored the role of irisin as a new pancreatic β-cell secretagogue and survival factor and its potential role in the communication between skeletal muscle and pancreatic β-cells under lipotoxic conditions. Recombinant irisin stimulated insulin biosynthesis and glucose-stimulated insulin secretion (GSIS) in a PKA-dependent manner and prevented saturated fatty acid-induced apoptosis in human and rat pancreatic β-cells, as well as in human and murine pancreatic islets, via AKT/BCL2 signaling. Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
2
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 26 publications
5
85
2
8
Order By: Relevance
“…Irisin is a PPARγ-coactivator-1α (PGCα)-dependent myokine that stimulates browning in subcutaneous adipose tissues and induces increased energy expenditure, which improves obesity and IR through the MAPK and ERK pathways [92,93]. Irisin also stimulates beta-cell survival and glucose-stimulated insulin secretion through the PGA pathway, and inhibits saturated fatty acid-induced apoptosis in pancreatic beta-cells [94]. A low level of irisin in mice with muscle-specific constitutive ROCK1 activation suppresses irisin production in muscles, decreasing browning in adipocytes and leading to impaired insulin sensitivity [95].…”
Section: Irisinmentioning
confidence: 99%
“…Irisin is a PPARγ-coactivator-1α (PGCα)-dependent myokine that stimulates browning in subcutaneous adipose tissues and induces increased energy expenditure, which improves obesity and IR through the MAPK and ERK pathways [92,93]. Irisin also stimulates beta-cell survival and glucose-stimulated insulin secretion through the PGA pathway, and inhibits saturated fatty acid-induced apoptosis in pancreatic beta-cells [94]. A low level of irisin in mice with muscle-specific constitutive ROCK1 activation suppresses irisin production in muscles, decreasing browning in adipocytes and leading to impaired insulin sensitivity [95].…”
Section: Irisinmentioning
confidence: 99%
“…Indeed, diabetic mice injected with irisin show better glycemic and lipid profiles . We have recently demonstrated that, following 2‐week daily administration of irisin intraperitoneally, mice display an improved glucose tolerance, as a result of enhanced glucose‐stimulated insulin secretion, and this is associated with increased insulin content, as well as larger pancreatic beta‐cell area and cell proliferation …”
Section: Introductionmentioning
confidence: 99%
“…8 We have recently demonstrated that, following 2-week daily administration of irisin intraperitoneally, mice display an improved glucose tolerance, as a result of enhanced glucosestimulated insulin secretion, and this is associated with increased insulin content, as well as larger pancreatic beta-cell area and cell proliferation. 10 In addition to the pancreas, the biological functions of irisin include metabolic effects on multiple other tissues, such as bone, 11,12 skeletal muscle, liver, and fat. 8 Furthermore, numerous studies reported that circulating irisin levels are reduced in patients with type 2 diabetes, while increased serum or plasma irisin levels correlate with pathological conditions of energy surfeit, such as overweight/obesity, polycystic ovary syndrome (PCOS), and metabolic syndrome, probably in response to deterioration of insulin sensitivity or to compensate an underlying irisin resistance.…”
mentioning
confidence: 99%
“…In addition, a recent study has shown that irisin suppresses apoptosis in β cells and islets under lipotoxic condition via modulation of protein kinase B/B-cell lymphoma 2 (BCL2) signaling pathway [23]. However, it has yet to be determined whether irisin can alleviate lipid metabolic disorder and pro-inflammatory actions in β cells under T2DM-like conditions.…”
Section: Introductionmentioning
confidence: 99%